PERHITUNGAN BEBAN PENDINGIN PADA RUANG PERTUNJUKAN LABORATORIUM SENI BUDAYA DAN FILM SMA NEGERI 1 GADINGREJO - Rizky July Rahamdi (2021)
The theater room of art culture and film laboratory Senior High School of 1 Gadingrejo is a room that has used as a venue for performing of arts and playing films created by creativity of student and as a develop of art culture and film for students and the other uses as venue for workshop and meeting room when a study visit from other school. To make a comfortable to do activities in the theater room has needed a air conditioning like good as desired. So, it has reached air conditioning like good have to install cooling machine equipment with a capacity that is due or comparable to the cooling load in the theater room. Therefore, be required to do a survey and calculation to find out the total of cooling load. The calculation of cooling load uses as method are CLTD (Cooling Load Temperature Difference), CLF (Cooling Load Factor), SCL (Solar Cooling Load). The results of the calculation of cooling load of the theater room at 12.00 WIB (Western Zone Time of Indonesia) with a room design temperature based on SNI (National Standardization of Indonesia) is 56864,82 Btu/hour (4,74 Ton Refrigerant). Based on the results of the total cooling load of the theater room that could be as recommended to install an existing cooling machine namely AC Split with a capacity of 2 PK/unit with the capability to absorb heat of 18000 Btu/hour so that the number of cooling machine units required is 3 units.